Work Sharing during the Great Recession New Developments and Beyond - Messenger, Jon C.; Ghosheh, Naj (Edward Elgar Publishing, 2013)
'Work sharing' is a labour market instrument devised to distribute a reduced volume of work to the same (or similar) number of workers over a diminished period of working time in order to avoid redundancies. This fascinating and timely study presents the concept and history of work sharing and explores the complexities and trade-offs involved in its use as both a strategy for preserving jobs and a policy for increasing employment. The expert contributors examine the resurgence in the use of work sharing as a job preservation strategy via country case studies of work-sharing programmes implemented across the globe during the Great Recession of 2008-2009. These studies clearly illustrate that work sharing has been successful as a crisis-response measure in a number of countries. Lessons learned and their implications are presented alongside prescriptions on how to design permanent work-sharing policies that would provide appropriate incentives to generate positive effects for employment and promote a sustainable and job-rich economic recovery. This enlightening book will prove invaluable to academics, researchers, students and policymakers in the fields of labour economics, public sector economics and social policy.